The Role of Dividend Policy as A Mediation from the Influence of Liquidity, Leverage, and Profitability on Company Value (Analysis of Food and Beverage Sub-Sector Manufacturing Companies Listed in the Indonesia Stock Exchange) - Sauh, Bartolomeus Oktavianus; Natsir, Mokh.; Yanti, Dyah Agustin Widhi (Global Health Science Group, 2022)
This study aims to analyze the role of dividend policy as a mediator of the effect of liquidity, leverage and profitability on firm value in the food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange. The data analyzed are quantitative data and secondary data derived from the performance reports of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange from 2015 to 2019. The sample selection used the purposive sampling method. The analysis technique uses multiple linear regression analysis techniques and path analysis (path analysis). Based on the results of research and discussion, it is known that liquidity and profitability have a positive and significant effect on dividend policy, while leverage does not affect dividend policy. Liquidity, leverage, profitability and dividend policy have a positive and significant impact on firm value. Liquidity and profitability through dividend policy have a positive and significant effect on firm value, while leverage through dividend policy does not affect firm value.